Pengaruh Model Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa di MIS Darul Ulum Kandau Ulu - Rodiah, Siti; Rojiah, Siti; Qoriah , Siti Nur (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on students’ critical thinking skills at MIS Darul Ulum Kandau Ulu. This research adopts a Classroom Action Research (CAR) approach with two cycles, where each cycle consists of planning, implementation, observation, and reflection. The subjects of this study were 25 fifth-grade students. Data collection was conducted through critical thinking tests, observations, and documentation. The results showed that the implementation of the PBL model could improve students’ critical thinking skills. In the first cycle, the average critical thinking score of students was 68, while in the second cycle, it increased to 82. This improvement indicates that the PBL model is effective in training students to think critically through systematic problem-solving. Therefore, the use of the Problem Based Learning model is recommended as a learning strategy to enhance students’ critical thinking skills at the elementary school level.